2019
DOI: 10.1002/lary.28284
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal afferent modulation of swallowing interneurons in the dorsal medulla in perfused rats

Abstract: Objectives The purpose of this study was to investigate the influence of laryngeal afferent inputs on brainstem circuits that mediate and transmit swallowing activity to the orofacial musculature. Methods Experiments were performed on 19 arterially perfused juvenile rats. The activities of swallowing interneurons in relation to their respective motor outputs in the hypoglossal and vagus nerves were assessed during fictive swallowing with or without concurrent laryngeal sensory stimulation at intensities of 20,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
(78 reference statements)
1
10
0
Order By: Relevance
“…SE are commonly used to record ENG from transected axons of various nerves in situ [ 34 , 40 , 45 , 46 ]. They provide very high-quality ENG signals that can be used to monitor the central breathing activity, and also to compute spike–trigger averaging in electrophysiological studies [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SE are commonly used to record ENG from transected axons of various nerves in situ [ 34 , 40 , 45 , 46 ]. They provide very high-quality ENG signals that can be used to monitor the central breathing activity, and also to compute spike–trigger averaging in electrophysiological studies [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our results demonstrated that both the and had a similar pattern. This pattern included a step increase in discharge at the beginning of inspiration, a ramp-like increase throughout the inspiratory phase, and a sharp decrease in PHR activity at the end of inspiration, reflecting a physiological PHR discharge [ 34 , 39 , 40 , 45 , 46 , 56 ]. Furthermore, high correlation coefficients were measured between and .…”
Section: Discussionmentioning
confidence: 99%
“…Single but not repetitive swallows were produced after QPZ injection, allowing swallow-breathing coordination and the effects of swallowing on central respiratory activity to be analyzed in situ. This method of pharmacological elicitation of isolated swallows represents an advantage over sustained electrical stimulation of the superior laryngeal nerves or injection of water into the pharyngeal cavity which resulted in repetitive swallows [ 8 , 10 , 12 , 13 ]. Most swallows were produced near the phase transition between central inspiration and the post-inspiratory phase of breathing, in agreement with previous experimental data in vivo [ 8 , 9 ] and in situ [ 12 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some investigations, the arterially perfused working heart-brainstem (in situ) preparation has been used as an advantageous experimental model to study swallowing and record brainstem neuronal activity [ 12 , 13 , 14 , 15 ]. However, few spontaneous swallows occurred in situ [ 16 ], and several methods were used to evoke swallowing, such as mechanical stimulation of the pharyngeal cavity [ 15 ], manual injection of water into the oral cavity [ 17 ] and electrical stimulation of the superior laryngeal nerves [ 13 , 14 ]. To our knowledge, a pharmacological method to enhance swallowing over a long period has not been tested in situ.…”
Section: Introductionmentioning
confidence: 99%
“…The full experimental procedures for the perfused brainstem preparation, including extracellular recordings of brainstem neurons as well as the recordings of various respiratory motor nerves was described in full detail previously. [23][24][25][26] Animals were deeply anesthetized with isoflurane (4% for induction, 1.5-2.5% for maintenance) vaporized in O 2 . The whole body was transected below the diaphragm and then the upper body was transferred into cold artificial cerebrospinal fluid (aCSF, 5 C) bubbled with a carbogenic gas mixture (95% O 2 and 5% CO 2 ).…”
Section: The Perfused Brainstem Preparation: Surgical Proceduresmentioning
confidence: 99%